Bortezomib-based treatment for multiple myeloma patients with renal impairment: A systematic review and meta-analysis of observational studies. Issue 46 (November 2016) - Zhu, Wanqiu; Chen, Wenming
Abstract: Background: Renal insufficiency is a common and severe complication of patients with multiple myeloma. The aim of this study was to evaluate bortezomib-based treatment for multiple myeloma patients with renal insufficiency. Methods: The Cochrane Library, Embase, PubMed, ISI, China National Knowledge Infrastructure, Chinese Biomedical Literature Service System, Chongqing VIP Database, and Wan Fang Data were systematically searched to identify observational studies from January 1, 2001, to December 31, 2015. Myeloma response rate and renal remission rate were pooled by using risk ratio and 95% confidence interval (CI). The Cochran Q and I statistics were used to assess heterogeneity. Sensitivity analysis was performed to test the feasibility of pooled results. Publication bias was conducted when included studies were ≥9. Furthermore, grades of evidence were performed to evaluate study quality. Results: Eleven retrospective cohort studies were included in the final analysis. The number of available studies and risk ratios (95% CI) were, respectively, 10 and 1.48 (95% CI: 1.28–1.71) for myeloma overall response, 6 and 3.69 (95% CI: 2.22–6.13) for myeloma complete response, 9 and 1.47 (95% CI: 1.28–1.69) for renal overall remission, and 8 and 1.49 (95% CI: 1.26–1.75) for renal complete remission. No significant publication bias was observed and sensitivity analysis confirmed the stability of results. The overall qualities of evidence were high for myeloma complete response and medium for the other 3 outcomes based on the Grading of Recommendations, Assessment, Development and Evaluation system. Conclusion: Current evidence indicated that bortezomib-based treatment could improve myeloma overall response (especially myeloma complete response) and renal overall remission (including renal complete remission).